2013
DOI: 10.1016/j.visres.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of postural constraints on eye and head latency during voluntary rotations

Abstract: Redirecting gaze towards new targets often requires not only eye movements, but also synergistic rotations of the head, trunk and feet. This study investigates the influence of postural constraints on eye and head latency during voluntary refixations in the horizontal plane in 14 normal subjects. Three postural conditions were presented, (1) sitting in a chair using only eye and head movements, (2) standing without feet movements and (3) standing with feet movement. Head-eye reorientations towards eccentric un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Such ankle stabilization is likely part of an anticipatory postural adjustment in preparation of a complex movement sequence (Assaiante et al 2000 ), in this case ultimately aiming to shift the eyes in space. Given that in conventional head-fixed saccadic experiments, anticipatory adjustments and assemblage of multisegmental synergies are not required, our EMG findings thus agree with the view that the long eye latencies observed in this paradigm relate to active delaying of the eye saccades until all anticipatory postural adjustments and segments are ready to go (Scotto Di Cesare et al 2013 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Such ankle stabilization is likely part of an anticipatory postural adjustment in preparation of a complex movement sequence (Assaiante et al 2000 ), in this case ultimately aiming to shift the eyes in space. Given that in conventional head-fixed saccadic experiments, anticipatory adjustments and assemblage of multisegmental synergies are not required, our EMG findings thus agree with the view that the long eye latencies observed in this paradigm relate to active delaying of the eye saccades until all anticipatory postural adjustments and segments are ready to go (Scotto Di Cesare et al 2013 ).…”
Section: Discussionsupporting
confidence: 88%
“…Finally, the timing of segmental activation within this motor synergy was further evaluated by recording the initiation of electromyographic (EMG) activity from several muscles involved in stepping. A top-down sequence of segmental movement initiation has been observed when subjects turn on the spot in upright posture with the eye starting to rotate first and the foot last (Hollands et al 2004 ), but data show that eye saccade initiation is considerably delayed when compared with data from sitting subjects (Scotto Di Cesare et al 2013 ). Therefore, we hypothesized that this saccadic delay is introduced in order to optimize the coordination between the large number of rotating segments and the anticipatory postural adjustments required before the onset of movement.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in biomechanics caused differences in eyemovement behavior, which was most evident in the results from our analysis of the Pasta task (Table 3, Figure 4a). Postural constraints have previously been found to affect eye behavior; specifically, Di Cesare et al (2013) have found that eye movements were delayed when whole-body rotations were used to fixate a target. As well, Freedman (2008) has shown that saccades increased in velocity as head movements were restricted.…”
Section: Biomechanics Of Movement Affect Eye-movement Behaviormentioning
confidence: 99%
“…Reed-Jones et al (2014) have reported similar eyemovement latencies to light cues in sitting and standing positions in older adults compared with the young. Interestingly, while not using an older adult population, a number of studies have reported longer eye-movement latencies in young participants during whole body movements executed in the standing position, suggesting that the CNS requires additional time to process eye movements in these situations (Hollands et al 2004;Anastasopoulos et al 2009;Di Cesare et al 2013). If postural constraints increase eye-movement latencies to target displacements in older adults over and above those of their younger counterparts, it may be predicted that they need to devote more attentional resources to the dual task of standing and fixating targets, as postural constraints increase.…”
Section: Introductionmentioning
confidence: 99%